2006
DOI: 10.1002/ca.20347
|View full text |Cite
|
Sign up to set email alerts
|

False tendons: An endoscopic cadaveric approach

Abstract: False tendons (FTs) have been extensively described and recognized by gross anatomic studies. However, in the clinical setting the recognition of FTs is limited to the use of echocardiography. We examined 200 formalin fixed adult hearts, with gross dissections. In addition, 90 of these specimens were also examined with ultrasonographic and endoscopic techniques. Gross examination was able to identify FTs in 128 (62%) specimens. The total number of FTs observed, was 248 and was classified into five types accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 12 publications
1
46
1
1
Order By: Relevance
“…In the autopsy study by Loukas et al [16] in which ultrasound and morphological assessment were combined, an alternative classification of FTs was proposed. Sensitivity of the echocardiographic examination was markedly lower than that of endoscopic assessment (40.3% vs. 100%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the autopsy study by Loukas et al [16] in which ultrasound and morphological assessment were combined, an alternative classification of FTs was proposed. Sensitivity of the echocardiographic examination was markedly lower than that of endoscopic assessment (40.3% vs. 100%).…”
Section: Discussionmentioning
confidence: 99%
“…In a pathology study by Grzybiak et al [8], the prevalence was about 40% and it was similar across all age groups. Loukas et al [16] reported on FT prevalence in a series of 200 gross pathology specimens amounting to 62%. Embryogenetic origin of FTs was not fully elucidated; the most probable mechanism involves displacement of conducting fibres into the LV lumen.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some hearts, false tendons or fascicular structures may traverse the ventricular cavity between the septum and free wall and include the intervening PM (the Figure). 19,20 Although the subject of the article by Yamada et al 8 was monomorphic ventricular arrhythmia, the PM has been implicated as a possibly related substrate for ventricular fibrillation. 21 Just as the fascicles may represent the trigger sites for ventricular fibrillation, could the PM house such triggers as well 22,23 ?…”
Section: Madhavan and Asirvathammentioning
confidence: 99%
“…Different from the tricuspid valve, there is no direct attachment of the mitral valve to the ventricular septum, although the papillary muscles are frequently connected to the septum or to the right fibrous trigone by false cords (Loukas et al, 2007). The length and the reciprocal ratio between papillary muscles and cords show individual variations, but some studies demonstrated similar annular-to-papillary muscle tip distances in the 2-, 4-, 8-, and 10-o'clock positions that also correlate with mitral annular diameter (Sakai et al, 1999) and which are relevant for the proper choice of cordal length during reparative surgery.…”
Section: The Papillary Muscles and The Tendinous Cordsmentioning
confidence: 99%
“…The major processes are: annular reduction (sphincteric mechanism), followed by the apposition of the mural leaflet against the elevated aortic leaflet (that functions as a trap door), reduction of all left ventricular dimensions and the subsequent creation of a pressure gradient between the ventricle and atrium that eventually brings the leaflets toward the annular plane. Many interesting details are emerging, such as the presence of a rich innervation (Marron et al, 1996) and contractile elements within the leaflets, the contribution of left atrial myocardium to annular dynamics (Glasson et al, 1997;Timek et al, 2002cTimek et al, , 2003b, the architecture of the left ventricular myocardium, the spatial disposition of the left ventricular trabeculae and papillary muscles (Loukas et al, 2007), and the presence of receptors in the structure of the leaflets.…”
Section: Normal Valve Closurementioning
confidence: 99%